Cognitive aspects in games workshops for learning a foreign language - Claudia Ferrareto Lopes; Francismara Neves de Oliveira (Universidade Estadual Paulista Júlio de Mesquita Filho, 2014)
The goal of the study was to analyze the cognitive aspects related to learning English as a foreign language, by means of games workshops with students of the 6th grade of elementary school from a state school in Londrina. The paper is grounded on Piagetian theory and is descriptive-interpretative study with a qualitative perspective. Two guiding questions motivate the study: what is the role of games workshops for learning English as a foreign language? In what way the cognitive processes are held in the games workshops for learning English? To meet the proposed goals, workshops were implemented with games containing the linguistic contents studied in English classes. The games workshops enabled the observation and analysis of the cognitive aspects involved in learning a foreign language. Results show that the games workshops promote the participation of the students motivating action and output, evidencing gaps on the knowledge and providing equilibration processes. Subjects are asked to produce outputs via games demands, thus evoking knowhow, as well as the thinking about their own products, suggesting a conscious-awareness process.